2012
DOI: 10.1155/2012/439617
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Erbium and Vanadium Diffusion in Porous Silicon Carbide

Abstract: Experimental data on diffusion of erbium and vanadium in porous and nonporous silicon carbide at 1700 and 2200°C have been used for modelling diffusion in porous SiC. It is shown that the consideration of pore structure modification under annealing via vacancy redistribution allows for satisfactory description of dopant diffusion. As expected, important contribution to the diffusion in the porous medium is found to be made by the walls of the pores: in SiC, the vacancy surface diffusion coefficient on the wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For these reasons, traditional diffusion technologies are ineffective. In a series of works, it was shown that porous structures were an effective medium for diffusion doping of both materials, and that the effective diffusion coefficients in porous SiC and GaN are much higher than the tabulated diffusion coefficients in non-porous forms of these materials [105][106][107][108][109].…”
Section: Dopant Diffusion In Porous Sicmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, traditional diffusion technologies are ineffective. In a series of works, it was shown that porous structures were an effective medium for diffusion doping of both materials, and that the effective diffusion coefficients in porous SiC and GaN are much higher than the tabulated diffusion coefficients in non-porous forms of these materials [105][106][107][108][109].…”
Section: Dopant Diffusion In Porous Sicmentioning
confidence: 99%
“…The knowledge gained about the mechanisms of diffusion made it possible to propose practically important methods for doping wide-gap semiconductors. It is shown that low-temperature diffusion of a compensating impurity, such as vanadium, in SiC makes it possible to fabricate semi-insulating layers demanded for power and high-frequency electronic devices based on SiC, and that a similar effect could be achieved by introducing deep levels provided by silicon vacancies [105,106]. Efficient doping of GaN with an acceptor impurity directly during epitaxial growth has been demonstrated using porous SiC substrates implanted with magnesium [107].…”
Section: Dopant Diffusion In Porous Sicmentioning
confidence: 99%